A study of the financially risk associated with cross border trading of equities and its effect to OSK investor / Nor Akmar Abdullah - Abdullah, Nor Akmar (Faculty of Business and Management, 2010)
This research studies on financially risk associated with cross border trading of equities and its effect to OSK investor. Foreign equities also known as foreign share is a cross border trades of securities or stock listing in the market beside home countries’ market. Foreign share offers wider choice of stocks and give greater opportunity to investor since it included ninety percent of the world’s total wealth in stock market. In the literature, there are many empirical studies to disclose the relationship between risk such as liquidity, investment, capital, exchange rate, market, currency, credit etc. and foreign equities. However, the scope of this study focuses on most common type of risk involves and its effect to OSKIB investor who trade beyond Malaysia stock exchange. This study will focus on financial risk that divide into translation and transaction risk. The objective of the study is to determine whether the risk involve in cross border trading of equities affect the investment return. As a result, this study found that financially risk of cross border trade affect return on investment of OSK investor. This outcome may improve the knowledge of financially risk of foreign share for OSKIB investor since this scope of study is new phenomenon in Malaysia.